Pendidikan Anti Korupsi Sebagai Pembentukan Karakter, Perilaku Individu Melalui Potensi Mahasiswa di Stikes Amanah: ANTI-CORRUPTION EDUCATION AS CHARACTER BUILDING AND INDIVIDUAL BEHAVIOR THROUGH STUDENT POTENTIAL IN STIKES AMANAH - Aminuddin, Andi Muh. Adam; Suhana, Suhana; Lestari, Dewi; Nurhaedah, Nurhaedah; Sangkala, Sangkala (Jurnal Ilmiah Amanah Akademika, 2023)
Anti-corruption education has an important role in solving the problem of corruption. It can be seen from the increasing number of corruption cases that are being displayed on various social media. This phenomenon must be prevented and eradicated so that it does not have an effect on the country's economy, the system of national values and the state ideology. This article examines anti-corruption education as character building that emphasizes free will, individual behavior through student potential. This study was conducted using qualitative methods and literature study with the object of analysis from various references to books, articles and other media. The results obtained were that anti-corruption education for students required the formation of a humanistic character, student knowledge about corruption, legal policies related to corruption cases and obedience and legal awareness of students in tertiary institutions to maintain a caring attitude towards the nation and state.